The repeated low-velocity impact response and damage accumulation of shape memory alloy hybrid composite laminates - Li Hao; Liu Kun; Tao Zhen; Ye Liqing; Xiao Wenkang (e-Polymers)
The repeated low-velocity impact responses of traditional glass fiber-reinforced composites and shape memory alloy (SMA) hybrid composites were explored in this work. The force–time/displacement and energy–time curves were compared based on the impact damage. The variations of impact mechanical features including contact peak force, maximum deflection, and absorbed energy were analyzed. The damage accumulation of the two kinds of composites was further assessed. Results showed that the damage tolerance and impact resistance of SMA hybrid composites were improved. The changes of dynamic mechanical responses were closely associated with the damage modes at different impact energies. The total energy absorption of SMA hybrid composites was much larger than that of traditional composites with more repeated impact numbers. Moreover, the damage accumulation of SMA hybrid composite was slower compared to traditional composite, while the improvement of SMA hybridization on the impact resistance of the composites was less obvious at higher impact energy.